2009
DOI: 10.1590/s1807-59322009000700012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Non-Invasive Methods for the Detection of Coronary Atherosclerosis

Abstract: BACKGROUND:Non-invasive detection of atherosclerosis is critical for its prevention.Objective:To correlate non-invasively detectable indicators of coronary atherosclerosis, or Coronary Artery Disease (i.e., classical risk factors, hs-CRP test results, carotid intima-media thickness, endothelial function, ankle-brachial index and calcium score by computed tomography) with the extent of coronary disease assessed by the Friesinger index from conventional coronary angiography.METHODS:We conducted a prospective stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 31 publications
(30 reference statements)
2
41
2
1
Order By: Relevance
“…Other studies have also shown that the triglyceride/HDL-c ratio is more predictive than the LDL-c level, including the Metabolic Syndrome in Active Subjects in Spain study, 23 the Boston Area Health Study, 24 the Women's Ischemia Syndrome Evaluation, 22 and the study by Bampi et al 10 Data from larger trials are also consistent with our findings. The Helsinki Heart Study showed that LDL-c was a poor predictor of myocardial risk, but that triglycerides and HDL-c were good predictors.…”
Section: Study Of the Use Of Lipid Panels As A Marker Of Insulin Resisupporting
confidence: 90%
See 1 more Smart Citation
“…Other studies have also shown that the triglyceride/HDL-c ratio is more predictive than the LDL-c level, including the Metabolic Syndrome in Active Subjects in Spain study, 23 the Boston Area Health Study, 24 the Women's Ischemia Syndrome Evaluation, 22 and the study by Bampi et al 10 Data from larger trials are also consistent with our findings. The Helsinki Heart Study showed that LDL-c was a poor predictor of myocardial risk, but that triglycerides and HDL-c were good predictors.…”
Section: Study Of the Use Of Lipid Panels As A Marker Of Insulin Resisupporting
confidence: 90%
“…9 In addition to being a good measure of insulin resistance, the ratio of triglycerides to HDL-c is a powerful predictor of CVD. [10][11][12][13] Yet insulin resistance, even when manifested by the metabolic syndrome, is often unrecognized in clinical practice. [14][15][16] The only American study that showed good recognition of the metabolic syndrome was based on a survey with only a 30% response rate.…”
Section: Introductionmentioning
confidence: 99%
“…Bampi et al observed that, Friesinger score 0-4 indicates less extensive disease and Friesinger score e"5 indicates extensive coronary atherosclerosis with extensive coronary artery disease. 25 In group I patients 56% had insignificant coronary artery disease and 44% had significant coronary artery disease defined by Friesinger index (n=100). In group II patients 6% had insignificant coronary artery disease & had 94% significant coronary artery disease.…”
Section: Discussionmentioning
confidence: 97%
“…[25][26][27] Female are less prone to developed IHD in premenopausal age due to protective role of estrogen, moreover smoking as a risk factor of IHD is less common in our country among female, which may explain male predominance of IHD. 28 The common risk factors for coronary artery disease in the present study showed that, smoking was the highest in Group-I followed by hypertension, family history of CAD, diabetes mellitus (DM) and dyslipidemia.…”
Section: Prolonged Qtc Dispersion and Leaman Scorementioning
confidence: 99%
“…8,9,[21][22][23] These two lines represent the lumen-intima and media-adventitia interfaces. There is currently a slight disagreement regarding the location at which the measurements should be taken, but recommendations for carotid ultrasound scanning protocols 14,15 were published recently in order to improve the power of clinical studies.…”
Section: Discussionmentioning
confidence: 99%